A new coincidence module using pulse-mixing method applied in the 4π(LS)-γ coincidence system with TDCR detector. (May 2020) - Ziemek, T.; Broda, R.; Dziel, T.; Listkowska, A.; Tymiński, Z.
Abstract: Application of a new coincidence module using the pulse-mixing method in the 4π(LS)-γ coincidence system with TDCR detector in the beta channel (TDCRG) is presented. The pulse-mixing method extended for the TDCR system with gamma channel was compared with the classical coincidence method where the coincidence resolving time is introduced. The characteristics of the resolving and dead time of the above two methods were investigated. The level of accidental coincidences in the system was determined. The new developed coincidence module was validated by activity measurement of a set of 51 Cr, 54 Mn, 60 Co, 65 Zn, 85 Sr and 134 Cs standards. Highlights: Application of a new coincidence module in the TDCRG system. The pulse-mixing method extended for the TDCR system with gamma detector. Good agreement of 51 Cr, 54 Mn, 60 Co, 65 Zn, 85 Sr and 134 Cs activity measurement. The level of accidental coincidence determined in the system.